DESKRIPSI VEGETASI HUTAN MANGROVE DI DESA PUNGKOL, KECAMATAN TATAPAAN - Hardy Senen; Marthen Th. Lasut; Johny S. Tasirin (Universitas Sam Ratulangi, 2017)
ABSTRACT Pungkol Village is an important area of mangrove forest located on the northern coastal part of North Sulawesi. The aims of this research was to describe mangrove plant species found at Pungkol Village area by Cencus Method. Research finding on 25 ha mangrove area showed that there were 17 major species group, which are Avicennia marina, Avicennia officinalis, Avicennia rumphiana, Aegiceras floridum, Bruguiera gymnorrhiza, Bruguiera parviflora, Bruguiera sexangula, Ceriops tagal, Ceriops decandra, Rhizophora apiculata, Rhizophora mucronata, Rhizophora stylosa, Sonneratia alba, Sonneratia ovata, Thespesia populnea, Xylocarpus granatum dan Xylocarpus moluccensis. The plants are grouped in 16 families, they are Avicenniaceae, Rhizophoraceae, Myrsinaceae, Sonneratiaceae, Meliaceae and Malvaceae. Rhizophoraceae has the highest number of species found (8 species), followed by Avecenniaceae (3 species). Keywords : Pungkol Village, mangrove forest, species description